Two new antimicrobial steroids and other constituents from the whole plant of Ludwigia abyssinica. (December 2022) - Meli, Arlette Sonkoue; Mabou, Florence Déclaire; Ngnokam, Claudia Darille Jouogo; Kembou, Alex Junior Ngoufack; Tamokou, Jean-De-Dieu; Matsuete, Germaine Takongmo; Voutquenne-Nazabadioko, Laurence; Tsopmo, Apollinaire; Ngnokam, David
Abstract: The genus Ludwigia belongs to the Onagraceae family and it encompasses seventy-five species of aquatic plants. The chemistry of this genus is scarcely investigated, although some studies have demonstrated the potential of Ludwigia leptocarpa to produce important bioactive compounds. Herein, we describe the phytochemical investigation of Ludwigia abyssinica A. Rich. Two new steroids named 3 β -formyloxy-5 α, 6α-dihydroxysitostane (Ludwigiaformyl A, 1 ) and 3 β, 6 α -diformyloxy-5 α -hydroxysitostane (Ludwigiaformyl B, 2 ), along with six known compounds, 3 β -formyloxysitost-5-en (3 ), 5 α, 6 β -dihydroxysitosterol (4 ), maslinic acid (5 ), oleanolic acid (6 ) and a mixture of two iridoids: linearin (7 ) and 1-epilinearin (8 ) were obtained from whole plant of L. abyssinica . The structures of the isolated compounds were established by extensive analysis of their spectroscopic and spectrometric data, which included HR-TOF-ESIMS, 1 D NMR ( 1 H, 13 C) and 2 D NMR ( 1 H– 1 H COSY, HSQC, HMBC and ROESY) and by comparison with data reported in the literature. The antimicrobial activities of extracts, fractions, and new compounds (1) and (2 ) were evaluated using broth microdilution method against fungi and bacteria strains. The MeOH extract and the ethyl acetate fraction displayed different degrees of antibacterial and antifungal activities (MIC = 32 – 512 µg/mL; MMC = 64 – 512 µg/mL) whereas compounds 1 and 2 showed moderate antimicrobial activities against Pseudomonas aeruginosa, Staphylococcus aureus, Escherichia coli, Shigella flexneri and Cryptococcus neoformans (MIC = 8 – 32 µg/mL; MMC = 8 – 64 µg/mL). Graphical Abstract: ga1 Highlights: Two new steroid derivatives trivially named Ludwigiaformyl A and B, were isolated from Ludwigia abyssinica. Their structures were characterized by extensive 2 D NMR studies. Six known compounds were also isolated from this plant. Antimicrobial activities were evaluated.